An evaluation of compassion‐focused therapy within adult mental health inpatient settings. (25th February 2021) - Stroud, James; Griffiths, Carys
Abstract : Objectives: This study aimed to examine the effectiveness of a compassion‐focused therapy (CFT) group in improving patient outcomes compared to those receiving treatment as usual (TAU) with a trans‐diagnostic population who are inpatients within an acute psychiatric ward. Design: Quantitative data were gathered as part of routine clinical practice within three adult psychiatric wards using the Clinical Outcomes in Routine Evaluation‐Outcome Measure (CORE‐OM) at admission and discharge and non‐standardized Likert scales pre‐ and post‐group sessions. Method: Between April and August 2017, the Acute Psychology Service (APS) gathered CORE‐OM admission and discharge data from inpatients across three acute wards ( n  = 32) whilst 249 pre/post‐group data sets were gathered from CFT group work undertaken on the inpatient wards. Current inpatients self‐allocated to receive either CFT or TAU based on their desire for psychological involvement. Those self‐allocating to receive psychological involvement ( n  = 19) were compared to those who did not ( n  = 13) across the four subdomains of the CORE‐OM: Wellbeing, Functioning, Problem/Symptoms, and Risk. The Likert scales included subdomains to evaluate changes in self‐compassion, compassion to others, and threat. Those receiving CFT group work also received TAU. Results: Significant improvements to all CORE‐OM subdomains were observed for those receiving CFT group input, in particular the Wellbeing and Functioning subdomains. Those receiving TAU only noted a significant improvement in the area of Risk whilst levels of Wellbeing were identical at admission and discharge with no improvements noted. Pre/post‐group results indicated significant results for areas of self‐compassion and compassion to others, whilst results by session for the threat subdomain are mixed dependant on session. Overall, all areas noted significant improvements. Session content was observed to be most effective for breathing and Mindfulness‐based sessions and those utilizing imagery techniques. Conclusion: Compassion‐Focused Therapy appears to be an effective group intervention for a trans‐diagnostic population within adult inpatient settings. Patient outcomes are positively improved across a range of areas whilst undertaking psychological input in the form of CFT group work whilst also receiving TAU during an inpatient admission. The use of the CFT model to address trans‐diagnostic difficulties supports targeting underlying psychological constructs in comparison to symptom treatment alone. Practitioner Points: Compassion‐focused therapy is a multi‐model approach designed to target high levels of self‐criticism. Previous research has demonstrated its effectiveness for a range of specific diagnosis; however, there is a limited research base with open groups and a trans‐diagnostic population. Groups can be structured with standalone sessions to accommodate the unpredictable admissions and discharge patterns of acute psychiatric wards. Group sessions focused around Mindfulness and Imagery yielded the greatest significant improvements to pre‐sessions scores. The provision of compassion‐focused therapy groups within trans‐diagnostic inpatient settings is feasible and has shown to significantly improve overall levels of distress and risk compared to those receiving treatment as usual. The lack of standardized Likert group measures limits the power of the study. Whilst a RCT would provide more reliable data, this was not possible as part of routine clinical practice for ethical reasons.